2023
DOI: 10.24331/ijere.1221364
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-service Teachers' Readiness for Online Learning on their Social Anxiety in E-Learning Environments

Abstract: The purpose of this research is to examine the effect of pre-service teachers' readiness for online learning on their social anxiety in e-learning environments. For this purpose, opinions of 409 students who continue their pedagogical formation education at a university in Turkey were taken, the answers of 369 students were included in the research, and the data of 341 students with standardized scores were analyzed. In the study, readiness for online learning was considered as the independent variable and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Some research found greater addictive use of social media among males (Ryan et al, 2014; Çam & Isbulan, 2012). However, ongoing studies suggested a higher prevalence of the addictive use of social media among females compared to males (Andreassen, 2015; Griffiths et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some research found greater addictive use of social media among males (Ryan et al, 2014; Çam & Isbulan, 2012). However, ongoing studies suggested a higher prevalence of the addictive use of social media among females compared to males (Andreassen, 2015; Griffiths et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Araştırmalar akademik öz yeterlik ile akademik başarı arasında olumlu ilişkiler olduğunu belirtmektedir(71,72). Bu açıdan değerlendirildiğinde ise ergenlerin sosyal medya bağımlılığı ile akademik başarıları arasındaki ilişkiyi inceleyen araştırmacılar(73,74) sosyal medya bağımlılık düzeyleri yüksek olan öğrencilerin akademik başarılarının düşük olduğu sonucuna ulaşmışlardır. Kirschner ve Karpinski (75) ve Rouis, Limayem ve Salehi-Sangari(76) ise ergenlerin sosyal medya kullanım süreleri ile akademik başarıları arasında olumsuz anlamlı ilişkiler bulunduğunu belirlemişlerdir.…”
unclassified